Molecular Detection of Antibiotics Resistance Genes in Burkholderia cepecia isolated from Diabetic foot infection - Maryam Riyadh Al-Muhanna1 , Mahdi Al-Ammar2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
This study aimed to isolate and diagnose Burkholderia cepetia from clinical specimens of diabetic foot andstudy the resistance of bacteria to antimicrobial agent in Najaf governorate from Augest 2019 to November2019, which includes 120 clinical specimens for both sexes with an age ranged between )35-70) yearsold. The diagnosis of bacteria isolates was based on microscopy, as well as the culture and biochemicalcharacteristics as an initial diagnosis. The final diagnosis by the Vitek-2 compact system .Burkholderia cepacia 8(6.6%). Antibiotic sensitivity test was examined by dick diffution method,Burkholderia cepacia isolates showed high level of resistance almost for all ?-lactam antibiotic classesunder study which included;, ceftriaxone, cefoxitin and Cefepime, with percentage of (100%); ticarcllinwith clavulalnic acide ,piperacllin , ceftazidime, tobramycine, ciproflaxcin and levofloxacin with percentageof (87.5%); aztreonam and amikacine with percentage(62.5); meropenem , imipenem and gentiamycin withpercentage of (37.5%).At molecular study, the investigated the presence of antibiotic-resistant genes (blaImp, blaOxa,blaKpc,blaCTX-M) using PCR technique and electrophoresis systems. 6/8 Burkholderia cepacia isolateswere with blaOXA and (6/8) of isolates carry blaCTX-M gene, all isolates of Burkholderia cepacia gavenegative result of blaIMP and blaKPC gene. Finally PCR analysis showed that the integron gene was (3/8%).